Cytonuclear disequilibrium and genetic drift in a natural population of ponderosa pine. - Latta, R G (2001)
We measured the cytonuclear disequilibrium between 11 nuclear allozyme loci and both mitochondrial and chloroplast DNA haplotypes in a natural population of ponderosa pine (Pinus ponderosa, Laws). Three allozyme loci showed significant associations with mtDNA variation, while two other loci showed significant association with cpDNA. However, the absolute number of individuals involved in any of the associations was small, such that in none of the nuclear-organellar combinations was the difference between observed and expected numbers >11 individuals. Patterns of association were not consistent across loci or organellar genomes, suggesting that they are not the result of mating patterns, which would act uniformly on all loci. This pattern of disequilibria is consistent with the action of genetic drift and with existing knowledge of the structure of this population and thus does not imply the action of other evolutionary processes. The overall magnitude (normalized disequilibrium) of associations was greater for maternally inherited mtDNA than for paternally inherited cpDNA, though this difference was neither large nor significant. Such significant disequilibria involving the paternally inherited organelle indicate that not only are there a limited number of seed parents, but the effective number of pollen parents is also limited.